1995
DOI: 10.1002/ar.1092410207
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the oviductal wall during passage of unfertilized cumulus‐Oocyte complexes in mice

Abstract: These results indicate that oocyte-cumulus cell complexes influence the structure of the oviductal wall during the passage in the oviduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In animals with a long luteal phase, movement of cilia is considered to be useful for transfer of the gametes from the ovary to the uterus [10,24]. In the mouse, however, relaxation of the muscle coat surrounding the oviductal epithelium was reported to aid in this transportation [25]. We observed that ciliated cells were dominant in diestrus and proestrus.…”
Section: Discussionmentioning
confidence: 83%
“…In animals with a long luteal phase, movement of cilia is considered to be useful for transfer of the gametes from the ovary to the uterus [10,24]. In the mouse, however, relaxation of the muscle coat surrounding the oviductal epithelium was reported to aid in this transportation [25]. We observed that ciliated cells were dominant in diestrus and proestrus.…”
Section: Discussionmentioning
confidence: 83%
“…This phenomenon, known as “cumulus expansion”, facilitates the detachment of the COC from the follicular wall, the extrusion of the COC during ovulation, 49 ) and its capture by the oviductal fimbria; 50 ) promotes the acrosomal reaction in spermatozoa; 51 ) and transports the ovulated COC in the oviduct. 52 ) Furthermore, we have clarified that granulosa cells express an inhibitor of the induction of meiotic resumption and that cumulus expansion interferes with this inhibitor to induce the resumption of meiosis in oocytes in mammals. 53 56 )…”
Section: The Intraovarian Mechanism Controlling the Induction Of Oocymentioning
confidence: 97%
“…Our approach will certainly facilitate the elucidation of gene expression profiles during the series of morphophysiological events that characterize the Mu¨llerian duct-derived organs during the estrous cycle. [38][39][40] In addition, our study indicates that the upper vagina of the laboratory mouse is a convenient model organ for addressing basic and applied questions concerning the process of cornification in a developing stratified squamous epithelium.…”
Section: Discussionmentioning
confidence: 80%